Factors Explaining Active vs Inactive Users of eLearning in a Blended Learning Context among University Students in Thailand - Thomas, Darrin (ASEAN Journal of Education, 2023)
The use of blended learning has continued to grow yet its impact in terms of how actively engaged students are is not as thoroughly investigated. Therefore, the purpose of this study was to identify active and inactive users of a learning management system within the context of a blended learning experience at a tertiary institution in Thailand. A sample of 288 participants (n = 288) was taken from the research site. Utilizing a cross-sectional survey design, academic performance, course satisfaction, gender, class level, major, and attendance were used to distinguish between active and inactive users. In terms of predicting active users, the linear discriminant analysis showed an accuracy of 72 %, as well as a sensitivity of 81 %, and a precision of 75 %. The effect size was moderate for academic performance and attendance when comparisons were made between inactive and active users of the learning management system. Active users had higher academic performance, lower tardies, and fewer absences than inactive users. This indicates that active students generally perform better not only in traditional instructional environments but also in a blended learning context.